A review on comparative analysis of antimicrobial activity of different metal and metal oxide nanoparticle-based fabric - Farah, Tahsin Anjum (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2020.